IMPACT OF MARKETING STRATEGIES ON CUSTOMER ADVOCACY FOR PUBLIC AND PRIVATE SECTOR BANKS - Uma Parvathy.S, Dr.R.Christina Jeya Nithila, (Chelonian Research Foundation, 2023)
This study addresses the gap in research regarding the impact of marketing strategies on customer advocacy in India's diverse banking sector, which includes public, private, and foreign banks. Employing quantitative methods, including a structured questionnaire and Structural Equation Modeling (SEM) via AMOS software, the research analyzed responses from 488 participants obtained through non-probability quota sampling.The key finding is a strong positive correlation between marketing strategies and customer advocacy across both public and private sector banks, with a notably higher impact observed in private banks. This indicates that while public sector banks are effective in their marketing strategies, there is potential for further enhancement, particularly in areas of innovation and personalization.The study underscores the importance of marketing strategies in fostering customer advocacy, which is crucial for customer loyalty and positive word-of-mouth, contributing significantly to a bank's growth and market share. It concludes that both public and private sector banks stand to gain considerably from refining their marketing approaches to boost customer advocacy. Recommendations for public sector banks include focusing on relationship marketing, digital marketing, and customer experience enhancement. Private sector banks, on the other hand, should concentrate on continuous innovation, personalization, and strengthening their digital presence. Keywords: Marketing Strategies, Customer Advocacy, Public Sector Banks, Private Sector Banks and Word-of-Mouth.